2011
DOI: 10.1007/s11665-010-9779-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Creep Behavior of P92 Steel Welded Joint

Abstract: Different regions of heat-affected zone (HAZ) were simulated by heat treatment to investigate the mechanisms of the Type IV fracture of P92 (9Cr-2W) steel weldments. Creep deformation of simulated HAZ specimens with uniform microstructures was investigated and compared with those of the base metal (BM) and the weld metal (WM) specimens. The results show that the creep strain rate of the fine-grained HAZ (FGHAZ) is much higher than that of the BM, WM, the coarse-grained HAZ (CGHAZ), and the inter-critical HAZ (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…At high temperature, the creep performance, fracture mechanisms and tensile deformation behavior of P92 steel have been well understood . An et al analyzed the creep behavior of different regions in P92 steel welded joint, results showed that fine‐grained heat‐affected zone had the highest creep strain rate. In addition, the influence of temperature and strain rate on tensile deformation and fracture of P92 steel were investigated by Choudhary et al In order to better understand the mechanical and microstructural stability of P92 steel under uniaxial tension, Giroux et al studied the phenomena of necking, damage, and grain size evolution.…”
Section: Introductionmentioning
confidence: 99%
“…At high temperature, the creep performance, fracture mechanisms and tensile deformation behavior of P92 steel have been well understood . An et al analyzed the creep behavior of different regions in P92 steel welded joint, results showed that fine‐grained heat‐affected zone had the highest creep strain rate. In addition, the influence of temperature and strain rate on tensile deformation and fracture of P92 steel were investigated by Choudhary et al In order to better understand the mechanical and microstructural stability of P92 steel under uniaxial tension, Giroux et al studied the phenomena of necking, damage, and grain size evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Though these modifications helped extend the life of weldment, they did not provide a permanent solution to this kind of a technically challenging problem. Several failures were reported to occur at the weld joint interfaces made with Ni-based filler materials [17][18][19][20]. Unfortunately, selection of a nickel-base filler material may not provide a fully satisfactory solution if the CTE difference between the two base metals is very significant or when the service conditions are demanding.…”
Section: Introductionmentioning
confidence: 99%
“…Involvement of environment corrosion, time-dependent creep, and the complex interactions between them makes precise lifetime prediction quite difficult. [24][25][26][27] However, this method has not been adopted in the investigation of welded joint's cyclic behaviour. [11][12][13][14][15] It is worth mentioning that Zhu 12 18 have done some systematic investigations, which are of high value to understand the microstructure evolution during LCF and CFI loadings.…”
Section: Introductionmentioning
confidence: 99%
“…A similar approach was used for magnesium welded joints by Karakas et al 22,23 Additionally, creep damage of ferritic steel welded joints has been investigated a lot by using this method. [24][25][26][27] However, this method has not been adopted in the investigation of welded joint's cyclic behaviour.…”
Section: Introductionmentioning
confidence: 99%